5-3(x-7)=26-2x

Simple and best practice solution for 5-3(x-7)=26-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(x-7)=26-2x equation:


Simplifying
5 + -3(x + -7) = 26 + -2x

Reorder the terms:
5 + -3(-7 + x) = 26 + -2x
5 + (-7 * -3 + x * -3) = 26 + -2x
5 + (21 + -3x) = 26 + -2x

Combine like terms: 5 + 21 = 26
26 + -3x = 26 + -2x

Add '-26' to each side of the equation.
26 + -26 + -3x = 26 + -26 + -2x

Combine like terms: 26 + -26 = 0
0 + -3x = 26 + -26 + -2x
-3x = 26 + -26 + -2x

Combine like terms: 26 + -26 = 0
-3x = 0 + -2x
-3x = -2x

Solving
-3x = -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-3x + 2x = -2x + 2x

Combine like terms: -3x + 2x = -1x
-1x = -2x + 2x

Combine like terms: -2x + 2x = 0
-1x = 0

Divide each side by '-1'.
x = 0

Simplifying
x = 0

See similar equations:

| 15+2x-3=2x+5 | | 5(4x+9)=9(2x+3) | | 0.5(14x+8)=6x+8 | | -4m-11=-3m-14 | | 6x+9x-21=105-6x | | -2k-5=-k+3 | | m-9m-8m-5= | | 1+x=x-5 | | 2x+6x+8=36 | | -3(m-8)=3 | | P=22p | | 225-6x=30x+21 | | -3m+16=32-7m | | 2+5x=42 | | 3f+2=4f+4 | | 60(12+2.5m)=1 | | 20k+100=10k+120 | | 4x+5(5+x)=-2 | | 2-x=5x+14 | | 6(-m-8)+4(6m+4)=2m+13-4m | | 4y+3-3y=6 | | 3r^2+2r-3=0 | | 5n+1/8=3n-5/4 | | -7x-5=-33 | | -1(3-10y)=12 | | 5p-7=2p-4 | | 4g+6=2g+14 | | 4x^2+16x-15=0 | | t+(-14)= | | 7-4*x=13 | | -4y+7=-21 | | 3b-4=5b-2 |

Equations solver categories